Analysis of digital transformation on the economic growth of culinary business In Makassar City - Nurcahyadi Nurcahyadi; Anas Iswanto Anwar; Sanusi Fattah (Jurnal Mantik, 2023)
The development of technology, information and the internet also extends to the business sector, where entrepreneurs take advantage of the internet to widely disseminate their business products and services. One of the business sectors that is growing rapidly at this time is the culinary sector. This is due to the large number of requests and the large number of opportunities that you get when you are in the online culinary business. One of the purposes of this research is to find out and analyze the effect of Innovation and Creativity on the economic growth of the culinary business in Makassar City. The method used in this research is descriptive research method using a quantitative approach. The results of the study can be concluded that there is a significant influence between innovation and creativity on the economic growth of the culinary business in Makassar City.